Monoclonal Antibodies Conjugated with Superparamagnetic Iron Oxide Particles Allow Magnetic Resonance Imaging Detection of Lymphocytes in the Mouse Brain - Alessandro Luchetti; Davide Milani; Francesca Ruffini; Rossella Galli; Andrea Falini; Angelo Quattrini; Giuseppe Scotti; Giancarlo Comi; Gianvito Martino; Roberto Furlan; Letterio S. Politi (Molecular Imaging)
We investigated the potential of antibody-vectorialized superparamagnetic iron oxide (SPIO) particles as cellular specific magnetic resonance contrast agents to image lymphocyte populations within the central nervous system (CNS), with the final goal of obtaining a reliable tool for noninvasively detecting and tracking specific cellular populations in vivo. We used superparamagnetic particles bound to a monoclonal antibody. The particle is the contrast agent, by means of its T 2 * relaxation properties; the antibody is the targeting vector, responsible for homing the particle to target a surface antigen. To investigate the efficiency of particle vectorialization by these antibodies, we compared two types of antibody-vectorialized CD3-specific particles in vivo. We successfully employed vectorialized SPIO particles to image B220 + cells in a murine model of B-cell lymphoma. Likewise, we were able to identify CD3 + infiltrates in a murine model of multiple sclerosis. The specificity of the technique was confirmed by immunohistochemistry and electron microscopy of corresponding sections. Our findings suggest that indirect binding of the antibody to a streptavidinated particle allows for enhanced particle vectorialization compared to covalent binding of the antibody to the particle.